Style recurrence for corporate identity using case-base reasoning - Chen, James YiJun. (2011)
As the product families of companies carry the corporate identities of the company to the consumers, it is of key importance to each corporation to establish a distinct corporate image to communicate corporate strategy to both internal and external audiences.